Competency management in the public sector : European variations on a theme - Horton, Sylvia; Hondeghem, Annie, 1960-; Farnham, David (IOS Press ; Co-publisher, International Institute of Administrative Sciences, IIAS ; Distributor in Japan, Ohmsha, 2002)
Designed for both practitioners and academics, this work seeks to inform the reader about the practice of competency management services in the public sector. It throws light on the origins and meanings of the concept and traces the competency movement from the 1980s in the UK and USA.
"University of Portsmouth; Instituut voor de Overheid."
Keywords: Civil service -- European Union countries -- Personnel management -- Case studies.; Management by objectives -- European Union countries -- Case studies.; Administrative agencies -- European Union countries -- Personnel management -- Case studies.; Strategic planning -- European Union countries -- Case studies.; Fonction publique -- Pays de l'Union européenne -- Personnel -- Direction -- Études de cas.; Direction par objectifs -- Pays de l'Union européenne -- Études de cas.; Administration publique -- Pays de l'Union européenne -- Personnel -- Direction -- Études de cas.; Planification stratégique -- Pays de l'Union européenne -- Études de cas.; POLITICAL SCIENCE -- Public Affairs & Administration.; Administrative agencies -- European Union countries -- Personnel management.; Strategic planning -- European Union countries.; Civil service -- European Union countries -- Personnel management.; Management by objectives -- European Union countries.; Administrative agencies -- Personnel management; Civil service -- Personnel management; Management by objectives; Strategic planning; European Union countries; Overheidsmanagement.; Management development.; Theorie en praktijk.; Case studies; Case studies.; Études de cas.